The Relationship Between Problem Solving Methods and Student Learning Outcomes - Wa Jumina; Syahrir Syahrir; Mahatma Mahatma (Indo-MathEdu Intellectuals Journal, 2020)
This study aims to determine the relationship between problem solving learning methods and student learning outcomes in trigonometry material. The type of research used in this study is descriptive quantitative, which is a study that aims to determine the magnitude of the relationship between problem solving learning methods and student learning outcomes in trigonometry material. The sample was selected using the cluster random sampling technique and obtained by 28 students. Research variables consist of problem solving methods (X) and learning outcomes (Y). The instruments used are tests and questionnaires. The test is used to determine student learning outcomes and questionnaires are used to determine the use of problem solving learning methods in the learning process. The data analysis technique used is Product Moment Correlation. The results of the data analysis obtained rhitung value = 0.7417 While the conversion results based on the rtabel value distribution table were obtained at the level of 5% which was 0.347 and at the level of 1 % of 0.478. So that it can be written into rvalue ≥ rtable or 0.7417 ≥ 0.347 at the level of 5% and rvalue ≥ rtable or 0.7417 ≥ 0.478 at the testing level of 1% or in other words, there is a strong relationship between problem solving learning methods and student learning outcomes in trigonometry material or a large coefficient of determination of 55.01%.